Curative Properties of Kencur (Kaempferia galanga L.) Extract on Mice (Mus musculus) Kidney Histopathology Exposed to Cigarette Smoke - Arianto, Intan Diah Safitri; Lastoaji, Firman; Sudjarwo, Sri Agus; Valentinus, Thomas Widiyatno; Hestiana, Eka Pramyrtha; Hamid, Iwan Sahrial; Herupradoto, Eduardus Bimo Aksono; Lovela, Aprinda Ratna (Universitas Airlangga, 2025)
The aim of this research was to investigate the therapeutic effects of Kencur (Kaempferia galanga L.) extract on kidney histopathological damage in male mice exposed to cigarette smoke. Twenty 8-week-old male mice were randomly divided into five treatment groups (n=5). The negative control group (C-) consisted of mice not given kencur extract or exposed to cigarette smoke, while the positive control group (C+) comprised mice exposed to cigarette smoke without kencur extract. Treatment groups included Treatment 1 (T1) administered 150 mg/kg BW of kencur extract, Treatment 2 (T2) administered 300 mg/kg BW, and Treatment 3 (T3) administered 600 mg/kg BW. Mice were exposed to cigarette smoke for 14 days. The data were analyzed using the Kruskal-Wallis test to evaluate overall differences among the treatment groups. Where significant differences were found (p<0.05), further pairwise comparisons were conducted using the Mann-Whitney test, confirming statistically significant differences between specific treatment groups. Treatment 3 (T3) was found to be the most effective in reducing histopathological damage in the kidneys of male mice. This study demonstrates that kencur extract effectively reduces histopathological damage in the kidneys of mice exposed to cigarette smoke, highlighting its potential as a protective agent against smoke-induced tissue injury.